Prozess des Hochleistungstrainings - am Beispiel Gerätturnen - Theiss, P. (Wiener Medizinische Wochenschrift, 1998)
A controlled, long-term training process, extensive medical treatment as well as a satisfying social and familiar environment are the key factors for a healthy development of young athletes in high level gymnastics.